2017
DOI: 10.1128/genomea.00491-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Serratia proteamaculans MFPA44A14-05, a Model Organism for the Study of Meat and Seafood Spoilage

Abstract: In this study, we present a draft genome sequence of Serratia proteamaculans MFPA44A14-05. This strain was isolated from a spoiled organic modified-atmosphere-packed beef carpaccio. The draft genome sequence will contribute to the understanding of the role of the S. proteamaculans species in meat and seafood spoilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…alvei is an ideal resistant-isolate candidate in any system. These traits can also be found in species of Shewanella [ 68 , 69 ], Serratia [ 70 , 71 ], Carnobacterium [ 72 ], Brochotrhix [ 73 , 74 ], and Kluyvera [ 75 , 76 ]. All of these bacteria can colonize multiple environments, and the ability to acquire resistance in any given environment represents a significant risk for human health.…”
Section: Discussionmentioning
confidence: 99%
“…alvei is an ideal resistant-isolate candidate in any system. These traits can also be found in species of Shewanella [ 68 , 69 ], Serratia [ 70 , 71 ], Carnobacterium [ 72 ], Brochotrhix [ 73 , 74 ], and Kluyvera [ 75 , 76 ]. All of these bacteria can colonize multiple environments, and the ability to acquire resistance in any given environment represents a significant risk for human health.…”
Section: Discussionmentioning
confidence: 99%
“…S. proteamaculans was positively correlated with the TBARS value and b* value, indicating that S. proteamaculans might promote lipid oxidation. Fougy et al [33] have reported that S. proteamaculans can produce lipase to promote fat oxidation and produce yellowing.…”
Section: Pca and Correlation Analysismentioning
confidence: 99%
“…Bacillus spp. [9] , Brochothrix thermosphacta [17] , and Serratia [18][19][20] isolated from meat and meat products could secret lipase and protease, exacerbating meat spoilage.…”
Section: Activities Of Collagenase and Lipasementioning
confidence: 99%